Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1128/jvi.00838-11
|View full text |Cite
|
Sign up to set email alerts
|

Cell-to-Cell Contact with Hepatitis C Virus-Infected Cells Reduces Functional Capacity of Natural Killer Cells

Abstract: The distinct feature of hepatitis C virus (HCV) infection is. On the other hand, inhibition of activating receptor expression on NK cell surfaces may also suppress NK cell responses (39). Because they are readily involved in the activation of resting NK cells (5), a reduced display of constitutively expressed activating receptors, such as NKG2D, NKp30, NKp46, DNAM-1, and 2B4, may dampen the functional capacity of NK cells to fight against viral infection. Cytokines secreted in response to HCMV infection indeed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
64
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 41 publications
6
64
1
Order By: Relevance
“…Our results, combined with previous studies indicating that HCV E2 molecules as displayed on HCV JFH1 virions do not inhibit NK cell functions (50), suggest that an HCV E2/NK CD81 interaction is not the primary cause of impaired NK cell functions mediated in vitro or in vivo by HCV-infected cells. Although HLA-E can be stabilized and upregulated by HCV core peptide (amino acids [35][36][37][38][39][40][41][42][43][44] and provides a ligand for inhibitory NK receptor NKG2A/CD94 (60), we and others did not observe increased expression of HLA-E on HCV-infected cells (52). Despite inhibition of ADCC, CD16 expression levels were also unaltered on NK cells exposed to HCV-infected cells.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Our results, combined with previous studies indicating that HCV E2 molecules as displayed on HCV JFH1 virions do not inhibit NK cell functions (50), suggest that an HCV E2/NK CD81 interaction is not the primary cause of impaired NK cell functions mediated in vitro or in vivo by HCV-infected cells. Although HLA-E can be stabilized and upregulated by HCV core peptide (amino acids [35][36][37][38][39][40][41][42][43][44] and provides a ligand for inhibitory NK receptor NKG2A/CD94 (60), we and others did not observe increased expression of HLA-E on HCV-infected cells (52). Despite inhibition of ADCC, CD16 expression levels were also unaltered on NK cells exposed to HCV-infected cells.…”
Section: Discussionmentioning
confidence: 51%
“…Although this ligand may interact selectively with NKp30, disrupted signaling through this receptor could also affect z-chain-dependent signaling through CD16 to decrease ADCC. A previous study by Yoon et al (52) showed that NK cytotoxicity and IFN-g production was reduced following an 18 h coculture with HCV-infected cells and noted a decline in NKp30 and NKG2D expression on NK cells. We did not observe a reduction in NKG2D expression on NK cells after a 5 h incubation with infected cells.…”
Section: Discussionmentioning
confidence: 95%
“…HCV affects NK cell activity through direct cell-to-cell interaction via CD81 or NK cell receptors or in an indirect manner via cytokine or TRAIL release (6)(7)(8)(9). HCV E2 glycoprotein is suggested to inhibit NK cells directly by cross-linking CD81 (6,10).…”
mentioning
confidence: 99%
“…Interestingly, NK cells, which represent 30%–50% of intrahepatic lymphocytes (compared with 5%–15% in the periphery), are involved in every stage of HCV infection (from spontaneous clearance in the acute infection, to treatment-induced HCV clearance) 6 8. They kill HCV-infected hepatoma cells through the release of the cytotoxic molecules perforin and granzyme and through surface expression of tumour necrosis factor (TNF)-related apoptosis-inducing ligand (TRAIL) 7 9. IFN-α-stimulated NK cells express TRAIL and kill HCV-infected hepatoma cells via TRAIL 7.…”
Section: Introductionmentioning
confidence: 99%